Οι συντελεστές διαμόρφωσης της ενταξιακής πολιτικής και της σχολικής ψυχολογικής υποστήριξης μαθητών/τριών με αναπηρία στο σχολικό πλαίσ - Βασιλειάδης, Ηλίας; Ρουσσάκης, Ιωάννης (Παιδαγωγική επιθεώρηση, 2020)
International tendencies and the dominant educational policy that is associated with special education is focusing on integration practices and the promotion of inclusive education. The purpose of the given investigation was to imprintthe thoughts of principals of special education school settings, regarding the currently applied educational status of special education inGreece. The researchers, through semi-structured interviews, aimed to designate the factors that contribute to forming the inclusion politics in general education classrooms of students with some form of disability. The content analysis of the data that were collected by the investigators, lead them in the conclusion that it is of high importance to consider the school culture as a significant factor of the degree of which students with disabilities can be included in general education and the quality of the cooperation that will be developed through the principles and the educational stuff.
Keywords: Disability and educational policy; principals of special education schools; inclusion of students with disabilities; school culture.